Increased microRNA-30a levels in bronchoalveolar lavage fluid as a diagnostic biomarker for lung cancer - Wen-Jun Zhu; Bo-Jiang Chen; Ying-Ying Zhu; Ling Sun; Yu-Chen Zhang; Huan Liu; Feng-Ming Luo (PeerJ, 2021)
Background MicroRNA-30a (miRNA-30a) levels have been shown to increase in the plasma of lung cancer patients. Herein, we evaluated the miRNA-30a levels in the bronchoalveolar lavage fluid (BALF) of lung cancer patients as a potential biomarker for lung cancer diagnosis. Methods BALF miRNA-30a expression of 174 subjects was quantified using quantitative real-time reverse transcription-polymerase chain reaction and compared between lung cancer patients and control patients with benign lung diseases. Moreover, its diagnostic value was evaluated by performing receiver operating characteristic (ROC) curve analysis. Results The relative BALF miRNA-30a expression was significantly higher in the lung cancer patients than in the controls (0.74 ±  0.55 versus 0.07 ±  0.48, respectively, p < 0.001) as well as in lung cancer patients with stage I–IIA disease than in those with stage IIB–IV disease (0.98 ±  0.64 versus 0.66 ±  0.54, respectively, p < 0.05). Additionally, miRNA-30a distinguished benign lung diseases from lung cancers, with an area under the ROC curve (AUC) of 0.822. ROC analysis also revealed an AUC of 0.875 for the Youden index-based optimal cut-off points for stage I–IIA adenocarcinoma. Thus, increased miRNA-30a levels in BALF may be a useful biomarker for non-small-cell lung cancer diagnosis.